Preparation of (3R)-quinuclidinol using heterogeneous biocatalytic hydrogenation in a dynamically-mixed continuous flow reactor - Cleary, Sarah E.; Kazantzi, Sofia; Trenchard, Joshua A.; Monedero, Martin; Allman, Jack W.; Lurshay, Tara C.; Zhao, Xu; Kenny, Michael B. C.; Reeve, Holly A. (Frontiers in Catalysis, 2023)
This work was carried out to understand if a heterogeneous biocatalytic hydrogenation system could be implemented in a slurry mode continuous flow reactor, as a ‘slot-in’ alternative to a metal/carbon catalyst with minimal process or chemical engineering development. Biocatalytic hydrogenation was compared to metal (Pd/C) catalysed hydrogenation for ketone to chiral alcohol conversion in both a continuous flow reactor (Coflore ACR, AM Technology) and analogous scaled down batch reactions. Initial results demonstrated that batch reactions can achieve high conversions in 30 minutes, with relatively low biocatalyst loadings, meeting critical criteria for operation as continuous slurry mode process. Further results demonstrated full conversion of quinuclidinone to (3R)-quinuclidinol in continuous flow under mild conditions (35 °C, 2 bar H2). On intensification of the process to higher substrate loading (50 mM), conversion was similar to with Pd/C, however the biocatalytic system achieved far higher turnover frequency and total turnover number (65 min-1 and 20,000, respectively) than the metal system (0.16 min-1, 37). Comparison to an analogous batch reaction highlights that the biocatalytic system has promise for further optimisation and intensification in the scalable Coflore ACR. Overall, biocatalytic hydrogenation is shown to offer a decarbonised biocatalytic route and a ‘slot-in’ replacement to metal catalysts for hydrogenation reactions in continuous flow reactors.